Implementasi SIA Berbasis Microsoft Access sesuai SAK EMKM dengan Metode Evaluasi TELOS (Studi Kasus UMKM TamahFood) - Muhammad Said Mubarok; Rahmanita Vidyasari (Warmadewa Economic Development Journal (WEDJ), 2025)
TamahFood is a micro-enterprise engaged in the food sector that faces challenges in its accounting information system, particularly in the preparation of financial statements. This study aims to design an accounting information system using Microsoft Access that meets the needs of the business and complies with the SAK EMKM standard. The research method used is descriptive qualitative with a case study approach in UMKM TamahFood. Data were collected through interviews, observation, documentation, and literature study. The system design follows the SDLC approach using the Waterfall model, which consists of five stages: requirements analysis, system design, implementation, testing, and maintenance. System modeling was carried out using ERD to represent the database structure and DFD to illustrate the data flow. The developed system includes transaction recording for orders and purchases, financial reporting in accordance with SAK EMKM, inventory reporting, as well as supplier and customer lists. The system evaluate and testing using the TELOS framewrok shows that it is feasible to implement from technical, economic, legal, operational, and scheduling aspects.